Review of: "Climate Change and Sustainability: A Comparative Case Study" - Morakot Muthuta (My University, 2023)
Potential competing interests: No potential competing interests to declare.The topic is very interesting and up to date.There would be useful for many countries that are facing the same problems.1.The auther should grouping important issues. Comparative study should provide table comparison toshow what India could improve to achieve goals like Sweden did.3. They should provide some important graph or infographic.
Keywords: Diverse Global Research Studies; Climate Change and Environmental Impact; Sustainable Development and Policies